Graphene-based electrochemical aptasensor for the detection of salmonella typhimurium / Shalini Muniandy - Shalini , Muniandy (2020)
Recent foodborne outbreaks in multiple locations necessitate the continuous development of highly sensitive and specific biosensors that offer rapid and sensitive detection of foodborne pathogens. The emergence of electrochemical aptasensor which is a compact analytical device with a combination of an aptamer as the biorecognition element integrated on the transducer surface created a breakthrough in the detection of foodborne bacterial pathogens. Graphene has emerged as a promising nanomaterial for reliable detection of pathogenic bacteria due to its exceptional properties such as high electrical conductivity, large surface to volume ratio, high mechanical strength and its unique interactions with DNA bases of the aptamer. However, the large surface area and strong interfacial interaction caused by van der Waals force of graphene result in severe aggregation in the composite matrix. These reduce the analytical performance, overall conductivity and electron transfer rate in aqueous conditions. The challenges identified in the process of fabrication of graphene-based aptasensor can be addressed through surface modification of graphene with electrochemically active material. As such, the present thesis sought to synthesize the novel reduced graphene oxide (rGO)-organic dye/metal oxide/polymer nanocomposite materials which were then coated on glassy carbon electrode (GCE) for the rapid, sensitive and selective detection of test organism, Salmonella enterica serovar Typhimurium. The strategy of using these nanocomposite materials is driven by the synergistic effect between the rGO and nanoparticles which essentially boosts the overall electrochemical activity and sensing performance of the sensors. The rGO and rGO-nanocomposites were synthesized using novel and one-pot simple chemical reduction method by using a minimal amount of reducing agent (hydrazine) which could minimize the defects created on graphene sheet and reduces the overall production cost. The electrochemical properties of the graphene-nanocomposites modified electrode were studied using electrochemical characterization techniques. Moreover, the interaction of the label-free single-stranded aptamer S. Typhimurium was monitored by differential pulse voltammetry analysis and this aptasensor showed high sensitivity and selectivity for whole-cell bacteria detection. Under optimum conditions, this aptasensor exhibited a linear range of detection from 108 to 101 cfu mL−1 with good linearity and a detection limit of 101 cfu mL−1. Furthermore, the developed aptasensor was evaluated with other strains of Salmonella and non-Salmonella bacteria. The results obtained showed good specificity and selectivity, respectively. The fabricated rGO-nanocomposite aptasensor was also exposed to artificially S. Typhimurium spiked chicken food samples. The results demonstrated that rGO-nanocomposite aptasensor possess a high potential to be adapted for the effective and rapid detection of a specific whole-cell foodborne pathogen by an electrochemical approach. Furthermore, the mechanism involving the interaction of the biorecognition element and bacterial target on the rGO-nanocomposite was also studied to understand the underlying detection strategy which will serve as guidance for the design, optimization and operation of graphene-based biosensors for future applications.